Discovery of a characteristic molecular signature by microarray analysis of whole-blood gene expression in workers exposed to volatile organic compounds - Song, Mi-Kyung; Song, Mee; Choi, Han-Seam; Park, Yong-Keun; Ryu, Jae Chun (Biochip journal, 2013)
The aim of this study was to determine the transcriptomic response in workers exposed to volatile organic compounds (VOCs). As blood is one of the most easily accessible sources of RNA for analyzing environmental exposure, we identified and validated characteristic gene expression profiles of human whole blood in patients exposed to VOCs to determine if the transcriptomic responses of circulating blood cells reflected exposure to environmental toxicants. The findings demonstrated that the characteristic molecular signatures can help discriminate and predict the toxicant type. To evaluate the changes in gene expression levels in workers exposed to VOCs (toluene [TOL] and trichloroethylene [TCE]), We analyzed the genomewide expression profiles of whole bloods of TOL & TCE exposed workers and unexposed healthy subjects. Unsupervised gene expression analysis resulted in a characteristic molecular signature for each toxicant, and a supervised analysis identified 9,724 outlier genes as distinct molecular signatures distinguishing VOC-exposed workers from healthy controls. Further analysis of the multi-classification revealed 378 genes as surrogate markers for predicting each VOC with 100% accuracy. Our results suggest that these expression signatures can be used as predictable and discernible surrogate markers for screening VOC exposure. Furthermore, the use of these markers can be more widely applied in combination with more traditional techniques for assessing and screening toxic exposure to environmental VOCs.